(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this essay I will attempt an immanent criticism of Axel Honneth´s “moral monism” from the standpoint of Moishe Postone´s categorial reading of capital. Honneth´s critics such us Nancy Fraser have pointed out that modern markets cannot be fully reconstructed in moral terms. On the basis of Postone´s immanent critique of capitalism, I will claim that it is possible to reconstruct how capitalist markets presuppose moral principles, but systematically distort their realization. Postones theory may ground a critique of the neutralization of moral consideration in the capitalist form of society. This categorial reading may, thus, alloud for a questioning of the systemic neutralization of moral concerns under capitalism.